2014
DOI: 10.3201/eid2011.140525
|View full text |Cite
|
Sign up to set email alerts
|

ESBL-ProducingSalmonella entericaSerovar Typhi in Traveler Returning from Guatemala to Spain

Abstract: We report a case of typhoid fever in a traveler returning to Spain from Guatemala that was caused by Salmonella enterica serovar Typhi which produced an extended-spectrum β-lactamase (ESBL). This finding demonstrates the presence of ESBL-producing S. enterica ser. Typhi strains in the Americas. Enhanced surveillance is necessary to prevent further spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
3
19
0
1
Order By: Relevance
“…In this study, a significant proportion of Salmonella species isolates were resistant to third generation cephalosporins. Similar findings have been observed in Europe from people who travelled from Asian countries [29, 30] and in Kenya [31]. However, these findings are in contrast with the previous study conducted three years ago in the same hospital which observed all Salmonella species to be susceptible to ceftriaxone [28]; suggesting the presence of emerging multidrug-resistant Salmonella species in Northwestern Tanzania.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, a significant proportion of Salmonella species isolates were resistant to third generation cephalosporins. Similar findings have been observed in Europe from people who travelled from Asian countries [29, 30] and in Kenya [31]. However, these findings are in contrast with the previous study conducted three years ago in the same hospital which observed all Salmonella species to be susceptible to ceftriaxone [28]; suggesting the presence of emerging multidrug-resistant Salmonella species in Northwestern Tanzania.…”
Section: Discussionsupporting
confidence: 81%
“…However, many hospitals follow the guidelines of the WHO and then switch to a fluoroquinolone when S. Typhi has been isolated from blood [30]. We identified no ESBL producing S. Typhi; other ESBL producing Salmonella have been reported from Latin America, but unlike the epidemiology of S. Typhi outside of the region, drug resistance appears not to be an issue [31,32]. This observation is probably associated with a lack of H58 (genotype 4.3.1) S. Typhi outside of Asia and Africa.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 74%
“…Strains of multi-drug resistant (MDR) Salmonella typhi with the haplotype H58 were found worldwide, and accounted for multiple outbreaks in endemic countries and single cases in international travelers. Moreover, Klemm and Colleagues [64] detected several resistance genes (extended-spectrum β-lactamase genes, and ESBLs) in extensively-drug resistant strains, previously detected in other enteric bacteria [65]. Resistance is mainly associated with cumulative mutations in quinolone resistance-determining regions (QRDR) encoding DNA gyrase (gyrA and gyrB genes) and topoisomerase (parC and parE genes) [61,66].…”
Section: Antimicrobial Resistance and Typhoid Fevermentioning
confidence: 94%